Determination of Employee Well-being of the Accreditation Team: Cumulative Impact Analysis of Accreditation Administration Demands and Work Stress Pressure at Nahdlatul Ulama University, Lampung - Wahyu Bagus Pramono; Meliyanti Meliyanti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The purpose of this study was to examine how accreditation administrative demands serve as a primary factor influencing the health of accreditation team employees, with work stress as an intermediary factor. This study involved all 29 members of the accreditation team, consisting of lecturers and educational staff, who were selected through a saturated sampling technique. A quantitative correlational approach was used as the survey method. Data were collected through an online questionnaire, and the SPSS program was used to analyze multiple linear regression. The results of the correlation analysis showed that accreditation administrative demands had a significant and strong positive relationship with work stress (r = 0.626; p = 0.000). However, with an R Square value of only 13.2%, a simultaneous F test indicated that accreditation administrative demands and work stress did not have a significant effect simultaneously on employee health. The results indicate that accreditation team members have strong psychological resources, commitment, and organizational social support to maintain their health amidst heavy administrative workloads.